Pelatihan Konseling Sebaya untuk Meningkatkan Mentalitas Para Atlet Disabilitas National Paralympic Committe (NPC) SUMUT - Asbi, Asbi; Hasibuan, M. Fauzi; Sari, Mawar (CERED Indonesia Publishing, 2025)
This study examines the effectiveness of peer counseling training in enhancing the mental resilience of disabled athletes from the National Paralympic Committee (NPC) of North Sumatra, in preparation for the XVII National Paralympic Week (PEPARNAS) in Solo, Central Java, 2024. The training program was based on an adaptive sports psychology approach and tailored peer counseling techniques for disabled athletes. Using a descriptive qualitative method, the study involved 20 athletes from various sports. Data was gathered through participatory observation during a three-day training session and in-depth interviews with athletes, coaches, and companions. Findings from thematic analysis of the data revealed improvements in emotional awareness, communication skills, and stress management. Additionally, five peer support groups were established, providing a sustainable system that participants found beneficial. The results indicate that peer counseling positively affects the mental resilience of disabled athletes, with recommendations to integrate such programs into the Paralympic athlete coaching system and develop specific modules for different disabilities.